A Platinum Highly Concave Cube with one Leg on each Vertex as an Advanced Nanocatalyst for Electrocatalytic Applications. Issue 7 (5th February 2015) - Lai, Jianping; Niu, Wenxin; Qi, Wenjing; Zhao, Jianming; Li, Suping; Gao, Wenyue; Luque, Rafael; Xu, Guobao
Abstract Platinum highly concave cubes with one leg on each vertex (HCCLV) enclosed by {7 5 0} facets were conveniently synthesized for the first time through a one‐pot solvothermal method in a mixed solvent of oleylamine and isopropanol containing platinum(II) acetylacetonate. This method can also be extended to the synthesis of Pt dendrite nanocubes at shorter reaction times. Preferential overgrowth may facilitate the formation of Pt HCCLV in the presence of oleylamine and isopropanol. The Pt HCCLV exhibit excellent electrocatalytic activity for the oxidation of methanol (7.76×) and ethanol (5.46×) compared to commercial Pt black. Furthermore, the Pt HCCLV show higher stability than Pt dendrite nanocubes and commercial Pt black. The Pt HCCLV also remarkably improve the electrochemiluminescence activity of the luminol/H2O2 system.